Pulmonary Complications in Patients with Severe Brain Injury - Kiwon Lee; Fred Rincon (Critical Care Research and Practice)
Pulmonary complications are prevalent in the critically ill neurological population. Respiratory failure, pneumonia, acute lung injury and the acute respiratory distress syndrome (ALI/ARDS), pulmonary edema, pulmonary contusions and pneumo/hemothorax, and pulmonary embolism are frequently encountered in the setting of severe brain injury. Direct brain injury, depressed level of consciousness and inability to protect the airway, disruption of natural defense barriers, decreased mobility, and secondary neurological insults inherent to severe brain injury are the main cause of pulmonary complications in critically ill neurological patients. Prevention strategies and current and future therapies need to be implemented to avoid and treat the development of these life-threatening medical complications.